2018
DOI: 10.1038/s41598-018-29445-z
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of glycocholic acid and taurochenodeoxycholic acid as phenotypic biomarkers in cholangiocarcinoma

Abstract: Although several biomarkers can be used to distinguish cholangiocarcinoma (CCA) from healthy controls, differentiating the disease from benign biliary disease (BBD) or pancreatic cancer (PC) is a challenge. CCA biomarkers are associated with low specificity or have not been validated in relation to the biological effects of CCA. In this study, we quantitatively analyzed 15 biliary bile acids in CCA (n = 30), BBD (n = 57) and PC (n = 17) patients and discovered glycocholic acid (GCA) and taurochenodeoxycholic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…Other measured BAs amount to 9% of total concentration. The high abundance of GCA, GCDCA, and TCDCA in the total bile composition of patients with cholelithiasis was consistent with the results reported for patients with benign biliary disease[23].…”
supporting
confidence: 90%
“…Other measured BAs amount to 9% of total concentration. The high abundance of GCA, GCDCA, and TCDCA in the total bile composition of patients with cholelithiasis was consistent with the results reported for patients with benign biliary disease[23].…”
supporting
confidence: 90%
“…Glycocholic acid is a secondary bile acid, and particularly high levels of bile acids have been implicated in the pathogenesis of liver diseases 19 . One study suggested that glycocholic acid and taurochenodeoxycholic acid 18 can be used as phenotypic biomarkers in cholangiocarcinoma 20 . In this study, glycocholic acid in plasma was observed to be positively correlated with pancreatic cancer, suggesting that bile acids might also be closely associated with pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our data reveal that the strong correlation between According to the Warburg effect 34 , most cancer cells employ aerobic glycolysis rather than oxidative phosphorylation to synthesize energy 35 . Proliferating cells divert glucose metabolites into anabolic processes, while glutamine is provided as a carbon 20 source for the TCA cycle 36 . Succinate, as an important intermediate of the TCA cycle, is also intertwined with metabolites of the glutamine metabolic pathway and plays a crucial role in tumourigenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have indicated that GCA, as a clinical marker to detect liver diseases including HCC, chronic active hepatitis, chronic active hepatitis and chronic active hepatitis (40), has numerous advantages compared with the traditional liver function tests, including alanine aminotransferase, aspartate transaminase and gamma-glutamyltranspeptidase (41,42). Therefore, GCA analysis can provide the basic information for diagnosis, treatment and prognosis of liver diseases, various biliary system diseases, including cholangiocarcinoma (43), intrahepatic cholestasis and alcoholic liver injury (39,44). HCC has a high morbidity and mortality rate.…”
Section: Discussionmentioning
confidence: 99%